Az iparjogvédelem heterogenitása - Csécsy, György (Debreceni Jogi Műhely, 2018)
Industrial property protection, in addition to copyright, is a specific group of protection instruments and forms of protection under intellectual property law. The area of industrial property protection covers a very wide range. On the one hand the copyright law is homogeneous and on the other hand the industrial law is heterogeneous. This statement is based on the fact that copyright is governed by a single law, copyright law and industrial law is governed by several laws. It is a feature of the technical nature of industrial property protection that these are intellectual creations and as such are under legal protection, which is implemented by the application of different legal institutions depending on the nature and level of creativity. It is noticeable that technical progress has accelerated considerably today and this process must be followed by industrial property law.